Analisis Motivasi Belajar Siswa SMP Negeri 1 Wonosari dan Potensi Intervensi melalui Dialog Socrates - Manggiasih Heri Febriansandy; Arbin Janu Setiyowati; Yuliati Hotifah (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
Learning motivation is a crucial factor influencing students' academic achievement and character development. This study aims to analyze the learning motivation level of seventh-grade students at SMP Negeri 1 Wonosari and explore the relevance of using the Socratic dialogue technique in guidance and counseling services. The study used a quantitative approach with a survey method, involving 90 students as respondents. The instrument used was a learning motivation scale based on the Self-Determination theory by Deci and Ryan, which includes aspects of intrinsic and extrinsic motivation. The results showed that 57.45% of students were in the medium motivation category, 25.53% were low, and 17.02% were high. All students showed a dominance of extrinsic motivation (100%), with no indication of intrinsic motivation. This finding indicates that students are highly dependent on external factors for learning. The Socratic dialogue technique is considered relevant because it can build students' motivation from within through reflective questions and critical thinking. The implications of this study provide recommendations for guidance and counseling teachers to develop reflective dialogue-based services to foster sustainable and independent learning motivation.